Economic assessment of urban watersheds: developing mechanisms for environmental protection of the Feijão river, São Carlos - SP, Brazil - Machado,FH (2014)
In order to determine the willingness of the population of São Carlos (a city in the state of São Paulo, Brazil) to pay for the environmental protection (WTP) of the Feijão River's watershed, the Contingent Valuation Method (CVM), as well as the bidding-games technique, were used. In October 2010, 280 questionnaires were applied to a probabilistic sample of the population. A multivariate logistic regression model was built, creating five scenarios adjusted to the age and probability to pay according to the significant variables found. Concerning the WTP, 56% of the interviewees showed willingness to pay a monthly amount using the water bill as a vehicle for this. The WTP average was 1.94 US Dollar (USD), with a standard deviation of 1.91 USD. The total annual amount for the scenario that considers the whole population over 18 years old was of USD 3,930,616.80. The main argument for the negative WTP was that the interviewees could not afford it (14%).